Optimal litigation strategies with signaling and screening - Philippe Choné; Laurent Linnemer (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper examines the strategic effects of case preparation in litigation. Specifically, it shows how the pretrial efforts incurred by one party may alter its adversary's incentives to settle. We build a sequential game with one-sided asymmetric information where the informed party first decides to invest, or not, in case preparation, and the uninformed party then makes a settlement offer. Overinvestment, or bluff, always prevails in equilibrium: with positive probability, plaintiffs with weak cases take a chance on investing, and regret it in case of trial. Furthermore, due to the endogenous investment decision, the probability of trial may (locally) decrease with case strength. Overinvestment generates inefficient preparation costs, but may trigger more settlements, thereby reducing trial costs.
Keywords: K41; 330; Case preparation; settlement; trial; signaling; Zivilprozess; Extensives Spiel; Schiedsgerichtsbarkeit; Signalling; Theorie